Islam Abangan dan Nasionalisme Komunitas Samin di Blora - Mukodi Mukodi; Afid Burhanuddin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
This study aimed at exploring the starting point of Islam Abangan and nationalism among Samin community in Blora regency. This research also aimed at exposing the resistance of Samin community Blora in recent time. For this research, qualitative approach and e phenomenological method were both used to get the accurate results. Relation between Islam Abangan and nationalism among Samin community in Blora were coherently intertwined and in harmony. The harmony were manifested through the daily practices of Samin community containing the teachings of Ki Samin Surosentiko. The c onsistency  of the community in carrying out the teachings of Ki Samin Surosentiko caused them still exist to survive amid the onslaught of modernism currents. Thus, local culture, and Javanese Islam were the means to strengthen the attachment of humanity, to strengthen the humanity affinity as well as the seeds of nationalism spirit, in the regional locality, including in Blora.